Fluorescence in bio-inspired nanotechnology: first as probe, then as function - Hannestad, Jonas (Springer theses, 2013)
This thesis describes the evolving field of DNA nanotechnology, focusing on how biological structures and mechanisms constitute a basis for the design of novel technologies. It discusses how self-assembled, nanometer-scale DNA constructs can be functionalized using fluorescent labeling, and how applications are based on fluorescence resonance energy transfer (FRET). --